Multiply and divide by h:
lim_(h->0) ((f(c+h^2)-f(c))/h) = lim_(h->0) h ((f(c+h^2)-f(c))/h^2)
Substitute eta = h^2, clearly when h->0 also eta ->0 and:
h = sqrteta for h >0
h= -sqrteta for h < 0
Then:
lim_(h->0^+) ((f(c+h^2)-f(c))/h) = lim_(eta->0) sqrt eta ((f(c+eta)-f(c))/eta)
As f is differentiable in c:
lim_(eta->0) ((f(c+eta)-f(c))/eta) = f'(c)
so:
lim_(h->0^+) ((f(c+h^2)-f(c))/h) = lim_(eta->0) sqrt eta lim_(eta->0)((f(c+eta)-f(c))/eta) = f'(c) lim_(eta->0) sqrt eta = 0
and similarly:
lim_(h->0^-) ((f(c+h^2)-f(c))/h) = -lim_(eta->0) sqrt eta lim_(eta->0)((f(c+eta)-f(c))/eta) = -f'(c) lim_(eta->0) sqrt eta = 0
Then:
lim_(h->0) ((f(c+h^2)-f(c))/h) = 0